Asessment of evaluation of transference support and training impact on the work of nurses - Lucelia Ferreira Lima Bastos; Maria Helena Trench Ciampone; Vera Lúcia Mira (Universidade de São Paulo, 2013)
OBJECTIVES: to assess the impact of the Training Course on Prevention and Treatment of PU, in width and depth; to observe and analyze the variables of transference support of training, offered by the organization and to verify the existence of the relationship between transference support and training impact. METHODS: this was a quantitative study, in which data were collected through the application of Likert-type instruments, conducted with 75 nurses participating in a training at a hospital organization in São Paulo city. Data were analyzed statistically. RESULTS: there was a positive impact in width and depth, and the variables of transference support were strongly related to the impact, and situational factors of support were the main predictors of impact. CONCLUSION: the results pointed toward pathways to redirect the practice of instructional actions in the work environment of individuals in the study scenario and in similar situations that occur in organizations.